2006
DOI: 10.1007/s10165-006-0528-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of handy rheumatoid activity score with 38 joints (HRAS38) in rheumatoid arthritis patients receiving infliximab

Abstract: The parameters involved in the Disease Activity Score of 28 joints (DAS28) are not mutually independent, and the evaluation excludes ankle and foot joints. We developed a new quantitative and comprehensive assessment of the activity of rheumatoid arthritis (RA), called the handy rheumatoid activity score, with 38 joints (HRAS38), to overcome these disadvantages of DAS28. Forty-six RA patients who recently completed a 1-year infliximab therapy were evaluated for DAS28 (C-reactive protein; CRP) and HRAS38 at 0, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
(31 reference statements)
2
11
0
Order By: Relevance
“…However, the overall efficacy at this dose in Japanese RA patients is acceptable, as previously described: remission in 11% and non-remission improvement (at least 50% improvement in arthritis and serum CRP level) in 41% [14]. Moreover, the clinical and radiographic efficacy of infliximab added to MTX 7-9 mg/ week in Japan [9,[15][16][17] was comparable to that seen in ATTRACT [18,19] and ASPIRE studies [20]. Because of the lack of available data concerning MTX doses in Japanese RA patients living abroad, it has not yet been determined whether a similar dose of MTX to that used in many other countries (10-25 mg/week) is also appropriate for Japanese RA patients.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, the overall efficacy at this dose in Japanese RA patients is acceptable, as previously described: remission in 11% and non-remission improvement (at least 50% improvement in arthritis and serum CRP level) in 41% [14]. Moreover, the clinical and radiographic efficacy of infliximab added to MTX 7-9 mg/ week in Japan [9,[15][16][17] was comparable to that seen in ATTRACT [18,19] and ASPIRE studies [20]. Because of the lack of available data concerning MTX doses in Japanese RA patients living abroad, it has not yet been determined whether a similar dose of MTX to that used in many other countries (10-25 mg/week) is also appropriate for Japanese RA patients.…”
Section: Discussionmentioning
confidence: 74%
“…M group than the E group at weeks 4 (p = 0.02), 8 (p = 0.009), 12 (p = 0.001) and 24 (p = 0.0003) with the Mann-Whitney U test. The improvement in the disease activity was also evaluated by the handy RA activity score with 38 joints (HRAS38), in which the cut-off values for low disease activity and high disease activity are 50 and 100, respectively [9]. The HRAS38 score is the cumulative sum of a global assessment of disease activity by the patient (0-100), a swollen joint score graded from 0 to 3 based on a 38-joint assessment by a physician (0-114), and the serum CRP level (mg/l).…”
Section: Efficacy Analysismentioning
confidence: 99%
“…Although the clinical efficacy and safety of infliximab therapy in Japanese patients with RA has now been explored [15,16], only a few reports have examined the effect of infliximab on structural damage [17]. In this report, we studied 67 RA patients among the 410 patients enrolled in the RECON-FIRM-2 study and analyzed the structural damage in these patients using the modified vdH-Sharp scoring method at 0 weeks as well as at 54 weeks after the start of infliximab therapy.…”
Section: Discussionmentioning
confidence: 97%
“…In a previous study, we demonstrated that the estimated yearly progression rate was extremely high in Japanese RA patients before the start of infliximab therapy [17], and that the progression rate was suppressed by treatment with infliximab for one year [17]. This data was collected at a single center, and the patients who were recruited for the study were longstanding RA patients who had been waiting for a long time for anti-TNF inhibitors to be approved.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, biological agents targeting TNF-a are effective not only in controlling synovial inflammation, but also in halting structural damage to the joints, contributing to better HAQ-DI values [11][12][13][14]. Indeed, in Japan, the efficacy of infliximab in the control of RA activity and the halting of radiographic progression has been demonstrated with even a relatively low dose of methotrexate (MTX) [15][16][17][18]. However, differences in the temporal changes between the HAQ-DI and the mHAQ score in RA patients actively receiving treatment with biological agents have not been elucidated.…”
Section: Introductionmentioning
confidence: 97%